The influence of student achievement on teacher turnover - Torberg Falch; Marte R?nning (Center for Economic Studies and ifo Institute (CESifo), 2005)
Evidence on teacher behavior is essential for the understanding of the performance of school systems. In this paper we utilize rich data to study the teachers? quit decision in Norway. We distinguish between decisions to move between public schools within school districts, to another school district in the same labor market region, across labor market regions, and whether to leave public schools. The results indicate that the quit propensity to all four destinations is negatively related to student performance. The result is qualitatively independent of whether student performance is measured by exam results or teacher graduation.
Keywords: I29; H42; J44; 330; teacher turnover; student achievement; family status; non-pecuniary factors; Lehrkräfte; Arbeitsmobilität; Schüler; Bildungsniveau; Schätzung; Norwegen